Postpartum Ovarian Vein Thrombosis After Coronavirus Disease - EKMEZ Murat; EKMEZ Fırat; DANE Cem (Journal of Clinical Case Reports and Images, 2022)
COVID-19 epidemic, described as a community health emergency by the World Health Organization, began in December 2019. COVID-19 is a source of deep vein thrombosis (DVT) because of hypercoagulation, blood stasis, and endothelium injury complications. This study reports a 26-year-old pregnant woman with coronavirus hospitalized with a left ovarian vein (LOV) thrombosis at Sultangazi- Haseki Training and Research Hospital in Istanbul. Risk classification for DVT disease is of crucial importance for the forecast of coronavirus.
Keywords: Deep vein thrombosis